2008
DOI: 10.1590/s1677-04202008000200008
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrogen cyanamide on the endogenous hormonal content of pea seedlings (Pisum sativum L.)

Abstract: Hydrogen cyanamide (HC) has been used to break bud and seed dormancy and to improve rooting in several species, responses usually associated with the action of plant hormones. However, very few studies have measured endogenous hormones after HC treatment. Therefore, pea (Pisum sativum L.) seedlings with two fully developed internodes above the first leaf were sprayed with 0, 0.1 and 0.3% (v/v) HC. Endogenous concentration of indole-3-acetic acid (IAA), abscisic acid (ABA), zeatin/zeatin riboside and N 6 (∆ 2 -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…apple) in areas with warm winters and insufficient chill hours. Hydrogen cyanamide, the active ingredient of Dormex, increases IAA and cytokinin (CK) levels (Guevara et al 2008) and inhibits catalases (Amberger 1961). Catalases degrade hydrogen peroxide, a crucial anti-microbial compound produced by infected plants to attack plant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…apple) in areas with warm winters and insufficient chill hours. Hydrogen cyanamide, the active ingredient of Dormex, increases IAA and cytokinin (CK) levels (Guevara et al 2008) and inhibits catalases (Amberger 1961). Catalases degrade hydrogen peroxide, a crucial anti-microbial compound produced by infected plants to attack plant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…A crosstalk between grape bud dormancy and plant hormones along with the bud break is a critical dilemma for grape production. Previously, Guevara et al (2008) , Mornya and Cheng (2011) , Okay et al (2011) examined the endogenous hormonal change during bud dormancy release process and demonstrated that regulation and control, occurrence and termination of dormancy were regulated by hormones. Different levels of endogenous abscisic acid (ABA) are linked with development and release of apical buds dormancy in plants ( Powell, 1987 ).…”
Section: Introductionmentioning
confidence: 99%
“…The relation of plant hormones and bud dormancy in additionally as bud break was a major down aspect for every theories and production practices. Seasonal changes in endogenous hormone during and after bud dormancy release was studied by many researchers (Guevara et al, 2008, Dong et al, 2009, Mornya and Cheng, 2011, Okay et al, 2011, Seif El-Yazal and Rady, 2014, Seif El-Yazal et al, 2014, 2018a, b, c &d). They found that the incidence, termination, regulation and management of dormancy were regulated by hormones throughout sufficiently winter chilling requirement.…”
Section: Introductionmentioning
confidence: 99%